CORPORATE GOVERNANCE DAN UKURAN KAP TERHADAP INTEGRITAS LAPORAN KEUANGAN - Alferos Jabbar Enggartyasto (2022)
This study aims to empirically examine the effect of corporate governance and the size of KAP on the integrity of financial statements. This study uses a population of companies with the Kompas 100 index listed on the Indonesia Stock Exchange for the period 2018-2020. This study uses quantitative methods with data obtained in the company's financial statements and company annual reports or using secondary data. The sample contained in this study as many as 65 companies using purposive sampling. The techniques used in the data analysis of this study were model specification test, classical assumption test, multiple linear regression test, and hypothesis testing using partial statistical test (t) using STATA version 16 application. The results showed that (1) independent commissioners had no effect on the integrity of the financial statements, (2) the audit committee has no effect on the integrity of the financial statements, (3) the size of the KAP has no effect on the integrity of the financial statements.